A proposal and verification of a software architecture based on LabVIEW for a multifunctional robotic end-effector - Anjos, José Marcos Silva; Coracini, Guilherme Kisseloff; Villani, Emília (Advances in engineering software (1992), 2013)
► We propose a control software architecture for discrete event systems with LabView. ► We applied it to a multifunctional end-effector of aircraft manufacturing industry. ► We verified it with a model checking approach and a model-based testing approach. ► The architecture successfully deals with integration of multiple functionalities. This paper proposes a software architecture based on LabVIEW for controlling discrete event systems. The proposed architecture is an adaptation of the producer–consumer design pattern. This work uses the control software of a multifunctional robotic end-effector as a test-bed for analyzing the applicability of the software architecture and its limitations and advantages. This case study demonstrates the effectiveness of the architecture for dealing with the integration of multiple functionalities in the control system. For this case study, the validation of the architecture is performed using two verification techniques: (1) a formal verification using timed automata and the UPPAAL model checker and (2) the CoFI (Conformance and Fault Injection) method for defining the set of test cases to check the software product. Both verification techniques identified errors that were introduced into the control system during the programming phase.